Subcutaneous Extended-Release Buprenorphine Use in Pregnancy - Craig V. Towers; Heather Deisher (Hindawi Limited, 2020)
Background. Opioid use disorder (OUD) in pregnancy is managed by medication-assisted treatment. Sublingual buprenorphine is one option, but subcutaneous extended-release buprenorphine (Sublocade®) is an alternate form administered in monthly injections. Through an extensive literature search, we did not find any prior publication on the use of Sublocade in pregnancy. Case. Two patients with OUD switched from sublingual buprenorphine to Sublocade. One patient received a total of eight injections and then discovered she was pregnant. Based on ultrasound dating, the last 5 administrations occurred during her pregnancy. The second patient received 6 injections with the last occurring at the time of her last menstrual period. Both declined further injections, as well as oral buprenorphine. Serial urine drug screens remained positive for buprenorphine through delivery in both cases. Neither the mothers nor the neonates experienced withdrawal symptoms or adverse outcomes. No birth anomalies were found. Discussion. Though further research is needed regarding the use of Sublocade in pregnancy, it is likely that other pregnancies will occur during this treatment modality. If this long-acting form of buprenorphine medication is found to be safe, it might play a role in managing some pregnant patients with OUD.